Initial testing (stage 1) of the curaxin CBL0137 by the pediatric preclinical testing program. Issue 4 (21st September 2016) - Lock, Richard; Carol, Hernan; Maris, John M.; Kolb, E. Anders; Gorlick, Richard; Reynolds, C. Patrick; Kang, Min H.; Keir, Stephen T.; Wu, Jianrong; Purmal, Andrei; Gudkov, Andrei; Kurmashev, Dias; et al.
Abstract: Background: CBL0137 is a novel drug that modulates FAcilitates Chromatin Transcription (FACT), resulting in simultaneous nuclear factor‐κB suppression, heat shock factor 1 suppression and p53 activation. CBL0137 has demonstrated antitumor effects in animal models of several adult cancers and neuroblastoma. Procedures: CBL0137 was tested against the Pediatric Preclinical Testing Program (PPTP) in vitro cell line panel at concentrations ranging from 1.0 nM to 10.0 μM and against the PPTP in vivo solid tumor xenograft and acute lymphocytic leukemia (ALL) panels at 50 mg/kg administered intravenously weekly for 4 weeks. Results: The median relative IC50 (rIC50 ) value for the PPTP cell lines was 0.28 μM (range: 0.13–0.80 μM). There were no significant differences in rIC50 values by histotype. CBL0137 induced significant differences in event‐free survival (EFS) distribution compared to control in 10 of 31 (32%) evaluable solid tumor xenografts and in eight of eight (100%) evaluable ALL xenografts. Significance differences in EFS distribution were observed in four of six osteosarcoma lines, three of three rhabdoid tumor lines and two of six rhabdomyosarcoma lines. No objective responses were observed among the solid tumor xenografts. For the ALL panel, one xenograft achieved complete response and four achieved partial response. Conclusions: The most consistent in vivo activity for CBL0137 was observed against ALL xenografts, with some solid tumor xenograft lines showing tumor growth delay. It will be important to relate the drug levels in mice at 50 mg/kg to those in humans at the recommended phase 2 dose.